'Lorenz Sterne' among German philosophers: reception and influence. Issue 2 (23rd February 2017) - Large, Duncan
ABSTRACT: Laurence Sterne has been read and enjoyed in the German-speaking world since his own lifetime, in excellent German translations by Johann Joachim Christoph Bode and others. His importance to the development of the German novel has been the focus of a number of studies, but his attractiveness to German-language philosophers has been much less noted. In a chronological survey from the late eighteenth to the late twentieth centuries, this article begins with the role Sterne reception plays in the German cult of sensibility ( Empfindsamkeit ) before focusing in turn on Hegel, Schopenhauer, Marx, Nietzsche, Benjamin, Wittgenstein, Lukács and Luhmann. Superior philosophical stylists such as Schopenhauer, Marx, Nietzsche and the early Lukács succumbed to the temptation to imitate surface features of Sterne's style, but the most interesting cases arise when philosophers have spent time reflecting on Sterne's thematic concerns as well as his formal innovations. There have been three main areas of interest: Sterne's characterisations and the question of peculiar individuality, Sterne as a sentimentalist and moralist, and 'Shandyan humour'. An attempt is made to distinguish between philosophers (such as Wittgenstein) who merely enjoyed reading Sterne, and those (such as Marx, Nietzsche and Luhmann) who can be described as more properly 'Sternean'.